Bhutan : 2009 Article IV Consultation-Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that Bhutan's fiscal policy has been anchored by keeping current spending below domestic revenue. Bhutan's large and volatile trade deficits have been offset by sizable foreign aid flows, resulting in a balance of payments (BOP) surplus and reserve accumulation. The BOP surplus has averaged about 8 percent of GDP over the last few years. Executive Directors have commended the authorities for the strong economic performance anchored by hydropower sector development, and supported by prudent economic management, firm donor support, and political stability.